The utilization of curative health care in Mozambique: does income matter? - Lindelow, M (CSAE (University of Oxford), 2004)
In Mozambique, easily treatable diseases such as malaria, diarrhea, and respiratory infections contribute to a heavy burden of disease. Notwithstanding efforts by the Mozambican government to promote access to health care, many who could benefit from simple cost-effective health care services do not currently receive treatment. Moreover, it is known that the utilization of health services varies considerably across spatial domains and socio-economic groups. This paper is concerned with understanding the determinants of utilization of curative health services, paying particular attention to the role of income. It provides a broad analytical framework for analyzing both the binary decision to seek formal health care in the event of illness, and the multinomial choice of health care provider. The results show that income is not an important determinant of health care choices in Mozambique. Rather, other factors, in particular education and physical access, are more important. Moreover, unlike in some studies, own (time) price elasticity does not vary notably with income. At a methodological level, the analysis shows that the general conclusions are robust to a number of estimation issues that are rarely addressed explicitly in the analysis of health care choices, including sample selection, the potential endogeneity of consumption, and cluster-level unobservables. For the analysis of provider choice, the paper demonstrates the merits of a 'flexible' behavioral model. In particular, the paper rejects some of the restrictions of the standard model of provider choice, and shows that both the level of the price elasticity and the extent to which the elasticity varies with income is sensitive to the empirical specification.